Fluorescence spectroscopy of DNA G-quadruplexes : ensemble and single-molecule measurements - Dao, Nguyen Thuan (2013)
Guanine-rich DNA can form structures called G-quadruplexes, which can be biologically important and also have potential applications in different fields including chemistry, nanotechnology and material science. G-quadruplexes are highly polymorphic and the activities of these molecules strongly depend on their structures. This study will focus on conformation and stability as well as excited state dynamics of G-quadruplexes using both ensemble and single-molecule fluorescence measurements, coupled with other techniques such as UV absorption, CD, and NMR spectroscopy. Our results on the conformation and stability of G-quadruplex DNAs as well as the photophysics of their excited states will help to understand more detail of this important form of DNA. The ensemble and single molecule fluorescence techniques which have been developed and employed in our work can be applied to study different forms of nucleic acid structures and their complexes, together with their interactions with other biomolecules such as proteins or small molecules.